PENGARUH PEMBERIAN TERAPI LATIHAN METODE SCHROTH TERHADAP SKOLIOSIS PADA USIA 10-12 TAHUN DI SEKOLAH DASAR NEGERI 01 KOTA JAMBI - Renni Hidayati Zein (Universitas Baiturrahim, 2017)
Introduction: Scoliosis is the backbone curved to the side, forming a S or C-shaped curve and may cause the hips and shoulders to tilt. Scoliosis is a common condition in early childhood and adolescence, as they grow rapidly. Scoliosis can be caused by birth defects, muscle spasms, inflammation or have different leg lengths. This condition can be permanent or temporary. The Schroth method is a physiotherapeutic processing system that uses isometric and other exercises to strengthen or lengthen the asymmetric muscle in the body of scoliosisMethods: Subjects in this study have been found 12 research subjects who are students of the State Elementary School 01 Jambi aged 10-12 years. Data retrieval is done by forward forward bending test. Each subject followed a pre test with forward bending test and measured using a skoliometer tool performed before treatment for 4 weeks, then each subject will follow post test with forward bending test and measured using a scoliometer after 4 weeks treatment. In the treatment will be given schroth practice training methods for 4 weeks with the frequency of exercise done every 3 times a week.Result: Based on the results of research with the theory on the discussion can be concluded that there is Influence Giving Schroth Method Exercise Therapy on Scoliosis at Age 10-12 Years at Primary School 01 JambiConclusion: Exercise Therapy Schroth method with regular frequency is an effective therapy for the management of scoliosis in children aged 10-12 years in order to prevent more severe scoliosis